Multi-Point Boundary Value Problems for Nonlinear Fourth-Order Differential Equations with All Order Derivatives (Communications in Mathematical Research, 2021)
By using fixed point theorem, multiple positive solutions for some fourth-order multi-point boundary value problems with nonlinearity depending on all orderderivatives are obtained. The associated Green's functions are also given.